1987
DOI: 10.1016/s0022-5347(17)44484-3
|View full text |Cite
|
Sign up to set email alerts
|

Urethral Pressure Variations in Healthy Females During Rest and Sleep

Abstract: Recent studies have shown the occurrence of rhythmic urethral pressure variations (UPV) in the normal female urethra in the awake state. The nature of these variations still needs further elucidation. In this study we investigated the changes in urethral pressure (UP) and in UPV as they occur in healthy females awake and asleep. UPV, intravesical-(IVP) and rectal pressure (RP), together with anal electromyography (EMG) and electroencephalography (EEG) were measured in 10 healthy fertile female volunteers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…If a causal link does exist between hormonal status and UI, the occurrence of UI can be hypothesized to covary with the hormonal changes occurring during menstrual cycles, which are not influenced by exogenous sex hormones. In clinical studies, the time position in the menstrual cycle has generally been found not to influence urodynamic parameters significantly, in either healthy fertile women (1, 14–18), or in women with known UI (14, 17). One study has demonstrated a slightly increased urethral length during the midcycle and the early luteal phase, whereas no covariation with urethral pressure was found (19).…”
mentioning
confidence: 99%
“…If a causal link does exist between hormonal status and UI, the occurrence of UI can be hypothesized to covary with the hormonal changes occurring during menstrual cycles, which are not influenced by exogenous sex hormones. In clinical studies, the time position in the menstrual cycle has generally been found not to influence urodynamic parameters significantly, in either healthy fertile women (1, 14–18), or in women with known UI (14, 17). One study has demonstrated a slightly increased urethral length during the midcycle and the early luteal phase, whereas no covariation with urethral pressure was found (19).…”
mentioning
confidence: 99%
“…Six expert opinion reviews were excluded . When multiple papers were published on the basis of a single patient cohort, only one paper of those, with the largest cohort, was included, others were considered duplicate and excluded . Twenty‐five papers met all predefined selection criteria and were included.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in UP that we found is perfectly compatible with this increase in the sympathetic tone. Moreover, Sorensen et al [1987] reported a decrease in UP during sleep in healthy women. Sleep on the one hand, vigilance and attention on the other hand, are two opposite physiological states, involving the reticular formation of the brain stem and, particularly, the Locus Coemleus (LC) [Lindsley, 1987;Elam et al, 1986;Yoshimura et al, 19881.…”
Section: Discussionmentioning
confidence: 96%